Relationship Timelines, Dyadic Interviews, and Visual Representations: Implementation of an Adapted Visual Qualitative Technique. (13th May 2021) - Sexton Topper, Patrina; Bauermeister, José A.
Increasingly popular in qualitative and mixed-methods research design, visual timelines help organize participants' life histories with an emphasis on temporality and the context in which important life events and experiences take place. Often, research using timelines focuses on individual participants. Yet, we know that life events, experiences, and decisions that individuals highlight in life history and narrative forms of research are relational in nature. Dyadic interviews allow for participant interaction, exploration of relationality, and the potential for increased breadth and depth in data collection. Recently, LGBTQ+ researchers have begun to evaluate dyadic approaches to timeline research. This paper describes a dyadic approach to timeline development designed to be combined with dyadic narrative interviews. We explain the data elicitation process, utility and value derived from the approach, and detail the development of post hoc linear, graphic timelines. This complementary approach leverages the strengths of dyadic narrative interviews and visual qualitative data synthesis and analysis to explore shared lives in context, highlighting their value as applied in research focused on a sample of sexual minority female couples (a community in which particular types of health disparities have been documented) from across the United States engaged in a series of clinically intensive shared decisions.